Unintentional Poisoning among Preschool Children in Jeddah, Saudi Arabia (2014-2016): A Retrospective Cohort Study - Iman Mohamed Wahby Salem (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Acute unintentional home intoxication in preschool-age children is a major cause of preventable morbidity and mortality. In the United States, 2012, around half of the youngsters younger than 6 years were accounted for as a poison occasion. Aim of the work: To estimate family and poison injury characters of preschool children who had unintentional home poisoning at poisoning department center under public health administration in Jeddah City, Saudi Arabia, during the duration between 2014-2016 and to recognize the relationship between unintentional poison' risk factors (personal, family character and injury factors) and poison types. Methodology: This retrospective cohort study was proceeded in the Jeddah poison center. All preschool children (0-5) years involved were reported as unintentional household harm (poisoning) cases at the chosen center. The questionnaire had developed and validated "from three public health experts," which was filed from center files and completed by a researcher telephone call to child-parent. Results: 41.5% of the affected children were occupied the (>12-24 months) age cluster. In addition, 62.6% of the participants were males, and most of the kids [44.4%] had a low social class. Conclusion: Inadvertent poisoning was commonly associated with age cluster (1-2 years), male gender, families with greater than three children, mother higher education, medicine poisoning of powder form, oral route, and at the morning time.